Advertising Discourse Language, Its Structural and Semantic Characteristics: Television Advertising as A Model - Radi, Badr Ben (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
This research paper discusses the subject of "advertising discourse language, its structural and semantic characteristics: television advertising as a model". The objectives of this paper focus on defining the concept of advertising discourse, studying its structural and semantic characteristics. The axes of this paper are: the concept of advertising discourse, the components of the advertising process and its types and statistics, and TV advertising discourse: its structural and semantic characteristics. With regard to the methodology, the descriptive-analytical approach will be adopted for an advertising body taken from Moroccan TV channels.